Os símbolos de Ap 17,1-18: uma forma de falar da realidade e de transmitir a esperança. - Soares, José Landes Marinho (2022)
This research aims to discuss the symbols of Ap 17,1-18 as a way of communicating the real and transmitting hope. One of the main features of Apocalypse is to present its message through symbolic language, in this sense, knowing the meanings of its symbols is of fundamental importance to understand its content. The objective of the study is to discuss the symbols contained in chapter 17 of the Apocalypse as a way of approaching reality and conveying hope. For this purpose, the bibliographic research methodology has been used as a means to ensure an up-to-date reflection, based on others critical research on the Bible. The text is divided into three chapters: the first chapter brings introductory and important aspects of the book of Apocalypse. The second chapter discusses the categories of real and symbolic as relevant elements for assimilating the meaning of the text. The third and last one makes an interpretative analysis of the text from its main symbols.